Broadband Enhanced Chirality with Tunable Response in Hybrid Plasmonic Helical Metamaterials. (17th February 2021) - Kilic, Ufuk; Hilfiker, Matthew; Ruder, Alexander; Feder, Rene; Schubert, Eva; Schubert, Mathias; Argyropoulos, Christos
Abstract: Designing broadband enhanced chirality is of strong interest to the emerging fields of chiral chemistry and sensing, or to control the spin orbital momentum of photons in recently introduced nanophotonic chiral quantum and classical optical applications. However, chiral light‐matter interactions have an extremely weak nature, are difficult to control and enhance, and cannot be made tunable or broadband. In addition, planar ultrathin nanophotonic structures to achieve strong, broadband, and tunable chirality at the technologically important visible to ultraviolet spectrum still remain elusive. Here, these important problems are tackled by experimentally demonstrating and theoretically verifying spectrally tunable, extremely large, and broadband chiroptical response by nanohelical metamaterials. The reported new designs of all‐dielectric and dielectric‐metallic (hybrid) plasmonic metamaterials permit the largest and broadest ever measured chiral Kuhn's dissymmetry factor achieved by a large‐scale nanophotonic structure. In addition, the strong circular dichroism of the presented bottom‐up fabricated optical metamaterials can be tuned by varying their dimensions and proportions between their dielectric and plasmonic helical subsections. The currently demonstrated ultrathin optical metamaterials are expected to provide a substantial boost to the developing field of chiroptics leading to significantly enhanced and broadband chiral light‐matter interactions at the nanoscale. Abstract : Chiral light‐matter interactions have an extremely weak nature, are difficult to be controlled and enhanced, and cannot be made tunable or broadband. This work tackles these important problems by experimentally demonstrating and theoretically verifying spectrally tunable, extremely large, and broadband circular dichroism from new hybrid dielectric and plasmonic nanohelical metamaterial configurations operating at the technologically important visible to ultra‐violet spectrum.